PEMBERDAYAAN EKONOMI BERBASIS MASJID (STUDI KRITIS PASAL 53, 54, DAN 55 PP. NOMOR 14 TAHUN 2014 TENTANG PELAKSANAKAAN UU NOMOR 23 TAHUN 2011 TENTANG PENGELOLAAN ZAKAT) (IAIN Tulungagung, 2017)
AbstractHistory records that, at the time of the Prophet Muhammad mosque plays an important role in the development of Islam. At that time the mosque not only as media ubuddiyah course, it is more vital role in education and empowerment of Muslims organized and set in the mosque. That is: education, propaganda, social and economic. Birth of law No. 23 of 2011 on the management of zakat provide an opportunity for the mosque to be the center of economic empowerment of the people. With a collector of Zakat Unit (UPZ) Amil Zakat Nasional (BAZNAS,) the mosque will become points zakat collection, donation and sedekahyang collected from the congregation of the mosque. Of the funds collected is used by the Collector Unit Manager Zakat (UPZ) or takmir mosque to empower and improve the welfare of the people.Keywords: Based Economic Empowerment Masjid, Zakat Management